Safety, efficacy, and drug survival of biologics and biosimilars for moderate‐to‐severe plaque psoriasis. (14th February 2018) - Egeberg, A.; Ottosen, M.B.; Gniadecki, R.; Broesby‐Olsen, S.; Dam, T.N.; Bryld, L.E.; Rasmussen, M.K.; Skov, L.
Summary: Psoriasis, a common disease affecting 2‐3% of the world's population, may in moderate‐to‐severe cases require systemic treatment with biological drugs (biologics). Treatment is usually permanent, but these drugs may loose their effect over time. When the patent for the original (originator) drug expires, other companies can produce a biosimilar, i.e. a drug that is very similar (but not completely identical, since biologics are derived from living human genes) to the originator. This Danish study compared safety, efficacy, and drug survival (i.e. how long patients stay on therapy) for five biologics: adalimumab, etanercept, infliximab, secukinumab, and ustekinumab. The study also compared the originator versions of etanercept and infliximab to their biosimilar versions. Data was examined from 3495 treatment series in 2161 patients. Drug survival was significantly higher for ustekinumab than for the other drugs. Secukinumab had the shortest survival and thereby also the highest risk of discontinuation of therapy. Adverse events also occurred the most frequently with secukinumab. Switching from an originator to a biosimilar version did not significantly affect drug survival. Among patients that obtained complete skin clearance, this occurred more rapidly for those treated with secukinumab as their first‐ever biologic. Over a 10‐year period, discontinuation of therapy occurred in 45·7% (adalimumab), 64·9% (etanercept), and 54·4% (infliximab) of patients. Ustekinumab and secukinumab have only been available for 8 and 2 years, respectively, during which time 30·3% and 28·8% of patients discontinued these therapies, respectively. Over time, response to therapy was generally highest for ustekinumab, followed by adalimumab. Abstract : Linked Article: Egeberg et al. Br J Dermatol 2018; 178 :509–519